Literature review penelitian pengembangan koleksi di perpustakaan digital - Farodisa, Nadia Nila; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Faculty of Communication, Padjadjaran University, 2024)
The era of information society demands that libraries transform from conventional libraries to digital libraries. In the effort to develop digital libraries, the focus should not solely be on increasing the number of collections but also on addressing more complex issues, including user needs analysis, policy formulation, collection selection, collection procurement, weeding, and evaluation. This study aims to examine the development of collections in digital libraries, which encompasses user needs analysis, collection development policies, collection selection, collection procurement, collection weeding, and collection evaluation. The research employs a narrative literature review methodology, analyzing ten references indexed in Google Scholar from the years 2013 to 2023. The findings indicate that in analyzing user needs, libraries assess visitor statistics, collect borrowing, and distribute surveys. Digital collection development policies may vary among libraries; however, principles of relevance, completeness, currency, collaboration, and user orientation can guide them. Collection selection is based on criteria established by the library, and digital collection procurement occurs through donations, grants, e-book purchases, e-journal subscriptions, and the digitization of printed collections. Digital collection weeding is conducted by examining usage statistics and the relevance of digital collections to user information needs. The evaluation of digital collections is performed through the distribution of questionnaires and an analysis of digital collection usage statistics. This study concludes that the development of digital library collections varies across libraries in terms of efforts and methods yet follows the same stages, from user needs analysis to evaluation.